Comparing the adverse outcomes of contraception failure between IUD and withdrawal methods - Majdfar, Zahra; Meshkat, Maryam; Tavana, Anahita; Tavana, Shahrzad; Amiri, Zohreh; Ehdaeevand, Farnaz; Saharkhiz, Nasrin; Fallahian, Masoumeh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of current study was to compare the adverse outcomes of pregnancy after failure of IUD (Intrauterine device) with the withdrawal method of contraception in order to predict and prevent such outcomes. Methods: In a retrospective cohort study, the adverse outcomes of 224 pregnancies (2 groups, 112 women each) were assessed following failure of the IUD or withdrawal methods of contraception (coitus interruptus). Data were analyzed and P values ≤0.05 were considered statistically significant. Results: Rates of spontaneous and induced abortion, ectopic pregnancy, and vaginal bleeding during second half of pregnancy were more common in the removed IUD group compared to the withdrawal method, differences however not significant. No fetal abnormality was observed in IUD group. Preterm birth (p= 0.045), preterm premature rupture of membrane (p= 0.01), and vaginal bleeding during pregnancy (p= 0.01), were more prevalent in the IUD group (retained and removed) compared to those using the withdrawal method. Conclusions: Considering the adverse outcomes, we knew women with pregnancy after failure of IUD were at an increased risk for such outcomes, compared to those using the withdrawal method; however the results of this research showed these adverse effects are not significant when pregnancy with IUD is detected earlier and IUD is removed during the early stage(s) of pregnancy.